Santri Care for Tuberculosis: Contextual Education and Early Screening in Islamic Boarding Schools - Marinda Dwi Puspitarini; Adyan Donastin; Paul Agus Dwiyanu; Muhammad Syaikhon; Luhqi Farhana Salsabila; Muhammad Ilham Said; Ain Darojah Siddiq Ramadhana (UKInstitute, 2026)
Tuberculosis remains a major public health issue in Indonesia, particularly in densely populated environments such as Islamic boarding schools. This community engagement program aimed to improve awareness, early detection, and prevention of tuberculosis through the “Healthy Adolescents Without TB” campaign at Hidayatulloh Al-Muhajirin Islamic Boarding School, Bangkalan. A total of 150 students participated in the activities, which implemented a participatory, faith-based health education model combining contextual learning, tuberculosis screening, and healthy behavior promotion. Interactive education sessions, audiovisual media, and testimonials from TB survivors significantly increased students’ understanding of disease prevention. Screening identified 13 students (8.6%) with chronic cough, 9 (6.0%) with weight loss, and 5 (3.3%) with night sweats, all referred for further evaluation at local health facilities. The integration of Islamic values into health messages enhanced cultural acceptance and motivated sustainable behavioral change. Overall, the program effectively strengthened adolescent health literacy and fostered active community participation, demonstrating that contextual, participatory, and faith-based education can serve as a replicable model to support Indonesia’s tuberculosis elimination strategy.